Two-dimensional ferroelastic topological insulator with tunable topological edge states in single-layer ZrAsX (X = Br and Cl). Issue 31 (26th July 2019) - Hu, Xiangting; Mao, Ning; Wang, Hao; Niu, Chengwang; Huang, Baibiao; Dai, Ying
Abstract : Here we predict theoretically that topological edge states can be significantly tuned by switching the ferroelastic ordering in a two-dimensional (2D) topological insulator. Abstract : Exploring and controlling topological edge states are crucial to both fundamental interest and device applications. Here we predict theoretically that topological edge states can be significantly tuned by switching the ferroelastic ordering in a two-dimensional (2D) topological insulator. By density functional theory, we identify that single-layer ZrAsX (X = Br and Cl) is a 2D ferroelastic topological insulator where the ferroelasticity and topological insulator phase appear simultaneously. The topological nontrivial property is confirmed by a nonzero spin Chern number C S = −1 and the appearance of gapless edge states. Remarkably, for engineering the topological edge states, low switching barriers of 21.11 meV for ZrAsBr and 32.70 meV for ZrAsCl are needed, indicating that the anisotropic properties of ZrAsX are experimentally achievable.